Repetitive-DNA elements are similarly distributed on Caenorhabditis elegans autosomes - Surzycki, Stefan A. (The National Academy of Sciences, 2000)
The positions of ≈4,800 individual miniature inverted-repeat transposable element (MITE)-like repeats from four families were mapped on the Caenorhabditis elegans chromosomes. These families represent 1–2% of the total sequence of the organism. The four MITE families (Cele1, Cele2, Cele14, and Cele42) displayed distinct chromosomal distribution profiles. For example, the Cele14 MITEs were observed clustering near the ends of the autosomes. In contrast, the Cele2 MITEs displayed an even distribution through the central autosome domains, with no evidence for clustering at the ends. Both the number of elements and the distribution patterns of each family were conserved on all five C. elegans autosomes. The distribution profiles indicate chromosomal polarity and suggest that the current genetic and physical maps of chromosomes II, III, and X are inverted with respect to the other chromosomes. The degree of conservation of both the number and distribution of these elements on the five autosomes suggests a role in defining specific chromosomal domains.